KUAT TEKAN BETON DENGAN BESI TULANGAN D13 - Rahelina Ginting (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
The reinforced concrete structures are structures that are very reliable in their current strength and are widely used in the construction of tall buildings and other constructions. The building structure requires medium quality concrete and high quality to compensate for the greater tensile stress used to support the structural components.As there is a need to an increase the quality of concrete by adding screw iron to fresh concrete, added material of screw concrete D13 was chosen which is well-used both in plate planning and practical columns to be used as added material aimed at increasing the tensile stress of the concrete. This research aims at finding the high effect of strong and sticky between concrete and threaded reinforced. Research method used is experiment by using sample in the form cylinder in which the diameter is 15 cm and 30 cm. Each specimen is 6 with variations of each 3 samples examined at 7 days and 3 other samples at 28 days where the quality of the concrete used was f’c 25 MPa which was medium quality concrete. The tool used is Universal Test Machine (UTM) with a pull out test. The sticky strength obtained from the 1986 Nawy Method is 8.044 MPa, the Oragun Et Al Method is 8.861 MPa, the Kim Method and the 2015 Park are 17.417 MPa